Ships and the development of maritime technology on the Indian Ocean - Barnes,Ruth,Ed; Parkin,David,Ed (Routldege, 2017)
Recognising the fundamental role both of shipping communities and the technologies crafted and shared by them, this book explores the types of ships, methods of navigation and modes of water-borne trade in the Indian Ocean region and the way they affected the development of distinctive settlements against a changing but strong sense of regional consciousness and identity.